2018
DOI: 10.1098/rsif.2018.0550
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modelling of the human lumbar facet capsular ligament: analysing spinal motion from the joint to the neurons

Abstract: Due to its high level of innervation, the lumbar facet capsular ligament (FCL) is suspected to play a role in low back pain (LBP). The nociceptors in the lumbar FCL may experience excessive deformation and generate pain signals. As such, understanding the mechanical behaviour of the FCL, as well as that of its underlying nerves, is critical if one hopes to understand its role in LBP. In this work, we constructed a multiscale structure-based finite-element (FE) model of a lumbar FCL on a spinal motion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“… 2013 ), spinal ligaments (Zarei et al. 2018 ; Damm et al. 2020 ), facet joints (Mengoni 2021 ) or for their coherent representation as a functional spinal unit (FSU) (Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“… 2013 ), spinal ligaments (Zarei et al. 2018 ; Damm et al. 2020 ), facet joints (Mengoni 2021 ) or for their coherent representation as a functional spinal unit (FSU) (Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“…Because subject‐specific structural information is not obtainable in vivo, this result points to a limitation of the proposed approach: the ability to describe detailed, small‐scale behavior of the tissue is limited by our ability to describe its small‐scale material properties. For instance, to study the effect of the macroscopic loading mechanisms on the local microscopic structural deformation surrounding a neuron in the ligament, a detailed structure‐based multiscale model would be needed 28,29,57 . If, however, the overall average strain in the ligament in different physiological motion is one's objective, then a simple NH model could generate an acceptable estimate of strain values.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, to study the effect of the macroscopic loading mechanisms on the local microscopic structural deformation surrounding a neuron in the ligament, a detailed structure‐based multiscale model would be needed. 28 , 29 , 57 If, however, the overall average strain in the ligament in different physiological motion is one's objective, then a simple NH model could generate an acceptable estimate of strain values. Our results are in agreement with previous studies 43 , 57 where they showed that the average magnitude of the axonal loading within a lumbar FCL changes concomitant with the magnitude of macroscopic tissue strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation